The evolution of pathways linking main streets and marketplaces to home-based business locations in Hanoi, Vietnam. Issue Volume 15:Issues 2(2022) (3rd April 2022) - Thai, Ha Minh Hai; Stevens, Quentin; Rogers, Judy
ABSTRACT: This paper explores the spatial complexities of Hanoi's urban form, with a focus on the evolution of the pathways linking the front door of individual households engaged in home-based income-generating activities, and the local main streets and marketplaces that provide opportunities for commerce. The pathway is an overlooked spatial element in existing urban studies, despite its critical importance in urban dwellers' everyday lives. At the city scale, a space syntax methodology is employed to examine the changing configuration of the street network in Hanoi across five historical periods. The analysis simulates the distribution of human movement across the network, highlighting the natural formation and changes to major economic hubs. The formation, evolution, and spatial character of these pathways are then examined at the neighbourhood scale, by employing three-dimensional mapping and semi-structured on-site interviews with Home-Based Business owners. The paper extends existing understandings of how urban form influences citizens' economic well-being.